2018
DOI: 10.1186/s12879-018-3118-5
|View full text |Cite
|
Sign up to set email alerts
|

Serological evaluation for Chagas disease in migrants from Latin American countries resident in Rome, Italy

Abstract: BackgroundChagas disease (CD) is a systemic parasitic infection caused by the protozoan Trypanosoma cruzi, whose chronic phase may lead to cardiac and intestinal disorders. Endemic in Latin America where it is transmitted mainly by vectors, large-scale migrations to other countries have turned CD into a global health problem because of its alternative transmission routes through blood transfusion, tissue transplantation, or congenital. Aim of this study was to compare the performance of two commercially availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…In fact, the factor most strongly associated with Chagas disease was being born in Bolivia. These results are consistent with other community-based seroprevalence studies [ 18 , 27 , 28 ]. People who had stopped studies after primary school were also at higher risk of having Chagas disease, in keeping with other studies of T. cruzi antibodies in blood donors in endemic countries [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, the factor most strongly associated with Chagas disease was being born in Bolivia. These results are consistent with other community-based seroprevalence studies [ 18 , 27 , 28 ]. People who had stopped studies after primary school were also at higher risk of having Chagas disease, in keeping with other studies of T. cruzi antibodies in blood donors in endemic countries [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that one of 10 participants in our screening program have Chagas disease, slightly higher than the pooled prevalence reported in a recent systematic review of Chagas disease in migrants in Europe [ 18 , 27 ]. All except one came from Bolivia, so one of five Bolivians had Chagas disease.…”
Section: Discussioncontrasting
confidence: 69%
“…The epidemiological pattern of CD has undergone substantial changes in last decades as a consequence of control campaigns in endemic countries, which have reduced vectorial and transfusional transmission [ 4 ]. Increasing international migration flows and more affordable traveling conditions from Latin America to non-endemic areas have contributed to epidemiology changes [ 5 , 6 ]. CD is no longer limited exclusively to the impoverished rural regions of Latin America; it is transformed into a global health concern affecting people worldwide in both endemic and non-endemic countries and placing 100 million people at risk for acquiring the infection [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has to be stated that 20 years later there is still a precarious lack of standardized policies in this regard. Previous studies named the absence of clear recommendations as well as standardisation in respect of screening, detection, diagnosis, and treatment as an important risk factor for inadequate care of individuals at risk [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the aforementioned limitations, this study highlights that even though Germany performed a pioneering implementation of screening, detection, diagnosis, and treatment of T. cruzi infections in regard to the knowledge that was available during the first period of the nearly two decades included in this study, currently there seems to be only a small percentage of individuals at risk of T. cruzi infection receiving adequate care. Previous studies show that a lack of guidelines is an important risk factor for inadequate care [ 21 , 22 ] and regard the implementation of a screening programme for T. cruzi infection among Latin American adults living in Europe a cost-effective strategy [ 10 ]. A prospective survey will be needed in the future to have a better estimation of the prevalence of CD in Germany.…”
Section: Discussionmentioning
confidence: 99%